2017
DOI: 10.1007/s00520-017-3605-z
|View full text |Cite
|
Sign up to set email alerts
|

Nothing left to chance? The impact of locus of control on physical and mental quality of life in terminal cancer patients

Abstract: Purpose To evaluate if Locus of Control (LOC) predicts various quality of life (QOL) and mental well-being measures among terminally ill cancer patients at the time of palliative care consult. Methods Multi-site analysis of patients with advanced cancer being seen as new patients in a Palliative and Supportive Care outpatient clinic. Patients completed the following surveys: Locus of Control Scale (LOC), Functional Assessment of Chronic Illness Therapy-General (FACT-G), Functional Assessment of Chronic Illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…In terms of the current state of research, it can be said that, to our knowledge, until now the moderating role of LoC has not been investigated with respect to COVID-19 related outcomes. Our findings confirm results of previous studies that established LoC as a resource to maintain and improve mental health [30,[34][35][36][37][38].…”
Section: Major Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of the current state of research, it can be said that, to our knowledge, until now the moderating role of LoC has not been investigated with respect to COVID-19 related outcomes. Our findings confirm results of previous studies that established LoC as a resource to maintain and improve mental health [30,[34][35][36][37][38].…”
Section: Major Findingssupporting
confidence: 91%
“…Cross-sectional and longitudinal studies from various international regions found that higher internal LoC and lower external LoC were moderately associated with greater mental health, lower situational stress, and lower mental distress, like depression and anxiety [30,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 – 33 ]). Cross-sectional and longitudinal studies from various international regions found that higher internal LoC and lower external LoC were moderately associated with greater mental health, lower situational stress, and lower mental distress, like depression and anxiety [ 30 , 34 38 ]. Studies on psychosocial factors during the COVID-19 pandemic also investigated the role of LoC.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Among patients suffering from such conditions, both recent and historical literature have established frequent associations between higher scores (indicating externalized LoC) on the General Locus of Control (GLoC) questionnaire and decreased physical and mental well-being, increased anxiety, and negative correlations with prognosis. [1][2][3][5][6][7][8][9][10] The questionnaire was developed by Rotter et al at the University of Connecticut as an instrument to measure and quantify a person's general sense of LoC. 1 The GLoC questionnaire has been validated and widely used in many different countries and languages, but still lacks a Brazilian Portuguese version.…”
Section: Introductionmentioning
confidence: 99%